Dynamics and Kinematics of the EUV Wave Event on 6 May 2019 - Ramesh Chandra; P. F. Chen; Pooja Devi; Reetika Joshi; Y. W. Ni (Galaxies, 2022)
We present here the kinematics of the EUV wave associated with a GOES M1.0-class solar flare, which originates in NOAA AR 12740. The event is thoroughly observed with Atmospheric Imaging Assembly (AIA) onboard Solar Dynamics Observatory (SDO) with high spatio-temporal resolutions. This event displays many features of EUV waves, which are very decisive for the understanding of the nature of EUV waves. These features include: a fast-mode wave, a pseudo wave, a slow-mode wave and stationary fronts, probably due to mode conversion. One fast-mode wave also propagates towards the coronal hole situated close to the north pole and the wave speed does not change when it encounters the coronal hole. We intend to provide self-consistent interpretations for all these different features.